KEEFEKTTFAN BEBERAPA BIAK RHIZOBIUM SEBAGAI INOKULAN PADA PERTUMBUHAN ALBIZIA PROCERA DAN A. SAPONARIA - LATUPAPUA, HJD.; RAHAYU, S.H.; ABDULKADIR, S. (BERITA BIOLOGI, 1988)
HJ.D. LATUPAPUA,S.H. RAHAJU & S.ABDULKADIR.1988. The effectiveness of some rhizobial strains as inoculants on the growth of Albizia procera and A. saponaria.Berita Biologi 3(8) 405 - 412.Four experiments have been carried out under green house conditions,using 0.5 gallon plastic pots, filled with 1.5 kg of sterile sands.The experimental design was completely randomized design with five replications.The first and second experiments were implemented on A.procera which consisted of 11 and 9 strains, lasted in 10 weeks respectively.The third and the fourth used 7 strains for each experiment,were implemented on A.saponaria,lasted in 12 and 16 weeks respectively.The results showed that all inoculated plants produced root nodules. In the experiments I and H,good results were demonstrated by strains number 34, 85 and 119, while strain Rsg showed very poor results.Rhizobium which showed poor results were strains Raf 1,Raf 2, Rap, Rss, Ri and Le. In the experiments III and IV, good results were demonstrated by strains 82 and 85,while very poor results were shown by strains Cg and Ri, poor results were shown by strains 34, 119 and Le.